Sodium-Glucose Co-transporter-2 Inhibitors and Nephroprotection in Diabetic Patients: More Than a Challenge - Provenzano, Michele; Pelle, Maria Chiara; Zaffina, Isabella; Tassone, Bruno; Pujia, Roberta; Ricchio, Marco; Serra, Raffaele; Sciacqua, Angela; Michael, Ashour; Andreucci, Michele; Arturi, Franco (Frontiers in Medicine, 2021)
Diabetic nephropathy is the most common cause of end-stage renal disease worldwide. Blood glucose and blood pressure (BP) control reduce the risk of developing this complication; however, once diabetic nephropathy is established, it is only possible to slow its progression. Sodium-glucose cotransporter-2 inhibitors (SGLT2is) are a novel class of oral hypoglycemic agents which increase urinary glucose excretion by suppressing glucose reabsorption at the renal proximal tubule. SGLT2is lower glycated hemoglobin (HbA1c) without increasing the risk of hypoglycemia and induce weight loss and improve various metabolic parameters including BP, lipid profile, albuminuria and uric acid. Several clinical trials have shown that SGLT2is (empagliflozin, dapagliflozin canagliflozin and ertugliflozin) improve cardiovascular and renal outcomes and mortality in patients with type 2 diabetes. Effects of SGLT2is on the kidney can be explained by multiple pathways. SGLT2is may improve renal oxygenation and intra-renal inflammation thereby slowing the progression of kidney function decline. Additionally, SGLT2is are associated with a reduction in glomerular hyperfiltration, an effect which is mediated through increased natriuresis and tubule-glomerular feedback and independent of glycemic control. In this review, we will focus on renal results of major cardiovascular and renal outcome trials and we will describe direct and indirect mechanisms through which SGLT2is confer renal protection.